Chronic voluntary oral methamphetamine induces deficits in spatial learning and hippocampal protein kinase Mzeta with enhanced astrogliosis and cyclooxygenase-2 levels. Issue 2 (February 2018) - Avila, Jorge A.; Zanca, Roseanna M.; Shor, Denis; Paleologos, Nicholas; Alliger, Amber A.; Figueiredo-Pereira, Maria E.; Serrano, Peter A.
Abstract: Methamphetamine (MA) is an addictive drug with neurotoxic effects on the brain producing cognitive impairment and increasing the risk for neurodegenerative disease. Research has focused largely on examining the neurochemical and behavioral deficits induced by injecting relatively high doses of MA [30 mg/kg of body weight (bw)] identifying the upper limits of MA-induced neurotoxicity. Accordingly, we have developed an appetitive mouse model of voluntary oral MA administration (VOMA) based on the consumption of a palatable sweetened oatmeal mash containing a known amount of MA. This VOMA model is useful for determining the lower limits necessary to produce neurotoxicity in the short-term and long-term as it progresses over time. We show that mice consumed on average 1.743 mg/kg bw/hour during 3 hours, and an average of 5.23 mg/kg bw/day over 28 consecutive days on a VOMA schedule. Since this consumption rate is much lower than the neurotoxic doses typically injected, we assessed the effects of long-term chronic VOMA on both spatial memory performance and on the levels of neurotoxicity in the hippocampus. Following 28 days of VOMA, mice exhibited a significant deficit in short-term spatial working memory and spatial reference learning on the radial 8-arm maze (RAM) compared to controls. This was accompanied by a significant decrease in memory markers protein kinase Mzeta (PKMζ), calcium impermeable AMPA receptor subunit GluA2, and the post-synaptic density 95 (PSD-95) protein in the hippocampus. Compared to controls, the VOMA paradigm also induced decreases in hippocampal levels of dopamine transporter (DAT) and tyrosine hydroxylase (TH), as well as increases in dopamine 1 receptor (D1R), glial fibrillary acidic protein (GFAP) and cyclooxygenase-2 (COX-2), with a decrease in prostaglandins E2 (PGE2) and D2 (PGD2). These results demonstrate that chronic VOMA reaching 146 mg/kg bw/28d induces significant hippocampal neurotoxicity. Future studies will evaluate the progression of this neurotoxic state.